Enhancement of the Optical Transmission System Utilizing a Dual-Function Remotely Pumped Erbium-Doped Fiber Amplifier - Al-Kaissi, Ahmed Wathik Naji (2006)
Optical fiber communication system is an active research area for its high demand especially in the long-haul communication system. A lot of work has been done to improve the optical transmission system (OTS) as a long-haul system using remotely-pumped Erbium-Doped Fiber Amplifier (R-EDFA) and Distributed Raman Amplification (DRA). Despite these achievements, there is still room for enhancements and developments to solve the existing system’s problems.